FRET-Protease-Coupled Peptidyl-Prolyl cis-trans Isomerase Assay: New Internally Quenched Fluorogenic Substrates for High-Throughput Screening. (August 2016) - Caporale, Andrea; Mascanzoni, Fabiola; Farina, Biancamaria; Sturlese, Mattia; Di Sorbo, Gianluigi; Fattorusso, Roberto; Ruvo, Menotti; Doti, Nunzianna
In this work, a sensitive and convenient protease-based fluorimetric high-throughput screening (HTS) assay for determining peptidyl-prolyl cis-trans isomerase activity was developed. The assay was based on a new intramolecularly quenched substrate, whose fluorescence and structural properties were examined together with kinetic constants and the effects of solvents on its isomerization process. Pilot screens performed using the Library of Pharmacologically Active Compounds (LOPAC) and cyclophilin A (CypA), as isomerase model enzyme, indicated that the assay was robust for HTS, and that comparable results were obtained with a CypA inhibitor tested both manually and automatically. Moreover, a new compound that inhibits CypA activity with an IC50 in the low micromolar range was identified. Molecular docking studies revealed that the molecule shows a notable shape complementarity with the catalytic pocket confirming the experimental observations. Due to its simplicity and precision in the determination of extent of inhibition and reaction rates required for kinetic analysis, this assay offers many advantages over other commonly used assays.